SUSCEPTIBILITY WEIGHTED IMAGING TECHNIQUE UTILITY IN DIVERSE NEUROLOGICAL ENTITIES - Vijetha Chanabasanavar; Sanjay Khaladkar; Darshana Dilip; Satvik Dhirawani; Vinay Kumar Parripati (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Background: Susceptibility Weighted Imaging (SWI) is a novel modality based upon GE (Gradient Echo) sequences that employ differences in susceptibility of various paramagnetic as well as diamagnetic substances that aid in the better diagnosis of various neurological entities such as intracranial tumors, vascular malformations, arterial stroke, venous hemorrhagic infarcts. Objective:To assess utility of SWI in various neurological diseases. Methods: The retrospective observational study was held in a tertiary care medical center in India in 2021. Multiple neurological diseases on SWI were analyzed in 100 patients with neurological complaints. The inclusion criteria included patient of all age group who presented with neurological signs and symptoms. The exclusion criteria included presence of post-operative non-compatible orthopedic hardware and patients with cardiac pacemakers, cochlear implants in situ. Results: The majority were males and > 60 years (23%) in age. Among 100 patients, most had tumors (18%), followed by trauma (16%), arterial stroke (15%), and hemorrhage (14%). Most of 14 patients with hemorrhage have intraparenchymal hemorrhage 9 (64.29%). There were10 patients with venous sinuses thrombosis and 15 cases with arterial stroke amongst whom most had middle cerebral artery thrombosis (46.66%). Most 13 patients with vascular pathologies had amyloid angiopathy 4 (30.77%). The majority of tumors were primary 15 (83.33%) with 10 (66.67%) newly diagnosed tumors, 11 (61.11%) tumors had a hemorrhage, 3 (16.67%) presented with calcification, and 4 (22.22%) had both hemorrhage and calcification. According to SWI grading of the tumor by intratumoral susceptibility score (ITSS), the majority were in grade III. On the correlation of SWI grading with MR Spectroscopy (MRS) and MR perfusion (MRP) study, 6 (100%) grade III patients showed hyperperfusion on MRP with raised choline/Creatinine ratio. SWI was better than CT (P<0.05) in detecting trauma, hemorrhage, cerebral venous sinus thrombosis, vascular pathologies, and tumors. Conclusion: SWI is a helpful imaging tool in neuroradiological practice and should be incorporated into standard procedures. It is beneficial in identifying hemorrhages, low-flow vascular abnormalities, diffuse axonal injury, and neurodegenerative illnesses. In addition, it is a supplementary sequence in the stroke by distinguishing calcium from hemorrhage in the brain and categorizing brain tumors.